An observer‐blinded randomized controlled pilot trial comparing localized immersion psoralen–ultraviolet A with localized narrowband ultraviolet B for the treatment of palmar hand eczema. (1st July 2018) - Brass, D.; Fouweather, T.; Stocken, D.D.; Macdonald, C.; Wilkinson, J.; Lloyd, J.; Farr, P.M.; Reynolds, N.J.; Hampton, P.J.
Summary: Background: Hand eczema is a common inflammatory dermatosis that causes significant patient morbidity. Previous studies comparing psoralen–ultraviolet A (PUVA) with narrowband ultraviolet B (NB‐UVB) have been small, nonrandomized and retrospective. Objectives: To conduct an observer‐blinded randomized controlled pilot study using validated scoring criteria to compare immersion PUVA with NB‐UVB for the treatment of chronic hand eczema unresponsive to topical steroids. Methods: Sixty patients with hand eczema unresponsive to clobetasol propionate 0·05% were randomized to receive either immersion PUVA or NB‐UVB twice weekly for 12 weeks with assessments at intervals of 4 weeks. The primary outcome measure was the proportion of patients achieving 'clear' or 'almost clear' Physician's Global Assessment (PGA) response at 12 weeks. Secondary outcome measures included assessment of the modified Total Lesion and Symptom Score (mTLSS) and the Dermatology Life Quality index (DLQI). Results: In both treatment arms, 23 patients completed the 12‐week assessment for the primary outcome measure. In the PUVA group, five patients achieved 'clear' and eight 'almost clear' [intention‐to‐treat (ITT) response rate 43%]. In the NB‐UVB group, two achieved 'clear' and five 'almost clear' (ITT response rate 23%). For the secondary outcomes, median mTLSS scores were similar between groups at baseline (PUVA 9·5, NB‐UVB 9) and at 12 weeks (PUVA 3, NB‐UVB 4). Changes in DLQI were similar, with improvements in both groups. Conclusions: In this randomized pilot trial recruitment was challenging. After randomization, there were acceptable levels of compliance and safety in each treatment schedule, but lower levels of retention. Using validated scoring systems – PGA, mTLSS and DLQI – as measures of treatment response, the trial demonstrated that both PUVA and NB‐UVB reduced the severity of chronic palmar hand eczema.